Unilateral micronychia associated with yellow nail. - Uwe, Wollina (European Journal of Pediatric Dermatology, 2025)
We present an 8 months-old otherwise healthy infant with a unilateral congenital micronychia combined with an acquired yellow nail on the neighboring digit of her right foot. The various associations of both nail conditions to syndromic and other underlying disorders are discussed. In our case, fortunately syndromic disorders could be excluded.